Effects of climate change on extreme rainfall in the municipality of Botucatu - SP - Adrien , Pedro Vitor Soares; Agostinho, Isaque Miyabara; Franco, José Rafael; Oliveira, Victor Crespo de; Dal Pai, Enzo (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – To study the influence of the effects of climate change on extreme rainfall in the municipality of Botucatu-SP-Brazil.Methodology – Application of statistical modeling in distinct periods of a 52-year series: the pre-climate change period and the full climate change period.Originality/Relevance – This work compares a previous study from 1999 with the latest years (up to 2022). The work verifies if there were alterations in the previous modeling.Results – There was an apparent increase in extreme rainfall of 6.8% according to the Gumbel model, and an increase of 70.9% for the GEV model.Theoretical/Methodological Contributions – The study of statistical meteorological distributions has already been well elaborated in the past. It is necessary to check the current validity of these models with current climate change data.Social and Environmental Contributions – This type of study provides tools for the correct dimensioning of structures such as bridges, culverts, terraces, and dams. With the scarcity of water on the planet, the correct dimensioning of hydraulic works is vital for the rational use of water. It also provides greater safety to hydraulic works.
Keywords: Extreme rainfall; Climate change; Statistical modeling; Gumbel; GEV